2011
DOI: 10.1590/s0103-90162011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation and isozyme diversity in Dioscorea alata L. landraces from Vale do Ribeira, Brazil

Abstract: Traditional growers of the Vale do Ribeira, São Paulo State, grow and make use of several D. alata landraces. This study assessed the genetic diversity of 16 landraces, using isozymatic and morphological markers and comparing them with 19 commercial varieties of D. alata. Their distribution in different levels of organization such as households and communities of the Vale do Ribeira was evaluated. Isozymatic analyses were performed with polyacrylamide (six systems) and starch gels (one system), while the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…The enzymes were extracted from recently expanded leaves (200 mg) from adult plants (6-8 months), and the procedures were performed according to Bressan et al (2011). Six systems were used with polyacrylamide gels: glucose-6-phosphate isomerase (GPI; E.C.…”
Section: Isozymatic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes were extracted from recently expanded leaves (200 mg) from adult plants (6-8 months), and the procedures were performed according to Bressan et al (2011). Six systems were used with polyacrylamide gels: glucose-6-phosphate isomerase (GPI; E.C.…”
Section: Isozymatic Analysismentioning
confidence: 99%
“…Previous research was carried out using morphological and isozyme analysis to study the genetic diversity of local varieties of D. alata L. that were cultivated by traditional farmers in Vale do Ribeira (Bressan et al, 2011). In Africa, the species complex D. cayenensis/D.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform a cluster analysis, we opted for the transformation of the morphological characteristics into binary data (presence, absence) (Bressan et al, 2011), which allowed of the similarity estimation through the Jaccard index. Based on the similarity matrix, a cluster analysis was applied by the UPGMA method (unweighted pair-group method using arithmetic mean) using the FDiversity statistical software program (Casanoves et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Monteiro and Peressin (2002) pointed out that flowering of the species is rare in Brazil. Bressan et al (2011) reported flowering in only 8.6% from a total of 35 D. alata accessions grown under experimental conditions in Piracicaba, São Paulo, and no seed was produced from the flowering plants. Lebot (2009) states that unfortunately, and in most cases, the varieties that have the best features, whether agronomic (compact tubers, for example) or palatability characteristics, are those that do not flower.…”
Section: Origin Of Dioscorea Alata Local Varieties and Their Usesmentioning
confidence: 96%
“…This study also showed that there is a clear regionalization in the assignment of popular names for D. alata local varieties, according to their morphology, uses or origin. The role of farmers in maintaining the local agro-biodiversity, whether in home gardens or fields, is important for the maintenance of the genetic diversity of yams and other crops over generations (Chair et al, 2010;Siqueira et al, 2010;Bressan et al, 2011;Veasey et al, 2012). However, for these varieties to be maintained at an on farm conservation basis, agroecological conservation policy goals must be considered, as well as more studies emphasising the importance of yams in rural areas.…”
Section: Origin Of Dioscorea Alata Local Varieties and Their Usesmentioning
confidence: 99%